2007
DOI: 10.1021/la700649w
|View full text |Cite
|
Sign up to set email alerts
|

Disubstituted Polyacetylene Brushes Grown via Surface-Directed Tungsten-Catalyzed Polymerization

Abstract: Disubstituted polyacetylene brushes were grown from modified silicon and quartz surfaces using a transition metal-catalyzed polymerization technique employing tungsten hexachloride/tetraphenyl tin (WCl6/Ph4Sn). The substrate surfaces were initially functionalized with terminal alkyne functional groups by using an alkyne-functionalized silane, O-(propagyloxy)-N-(triethoxysilylpropyl) urethane, as a surface coupling agent. Surface polymerization of 5-decyne under microwave irradiation at 150 degrees C for 30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…35 Recently, Carter et al have successfully reported the grafting of disubstituted polyacetylene brushes grown from modified silicon and quartz surfaces using a transition-metal-catalyzed polymerization technique. 36 The conventional method for preparing hole-transport polymer layer films involve solution-casting and spin-casting. 37,38 The problem with this method is that the electroluminescent active polymer layer is also spin-cast on top of the hole-transport layer, resulting in dissolution of the former film.…”
Section: Introductionmentioning
confidence: 99%
“…35 Recently, Carter et al have successfully reported the grafting of disubstituted polyacetylene brushes grown from modified silicon and quartz surfaces using a transition-metal-catalyzed polymerization technique. 36 The conventional method for preparing hole-transport polymer layer films involve solution-casting and spin-casting. 37,38 The problem with this method is that the electroluminescent active polymer layer is also spin-cast on top of the hole-transport layer, resulting in dissolution of the former film.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, few such methods exist. [1][2][3] Direct electropolymerization of a conjugated monomer from an electrolyte solution is the most common and versatile technique available at present. While this technique is simple in execution, allows for control of film thickness by varying the time and oxidation potential, and can be used on a variety of monomers, it tends to produce insoluble films with highly irregular morphologies as well as regioirregular polymers.…”
mentioning
confidence: 99%
“…One area where microwave‐assisted polymerization has demonstrated excellent utility is in the formation of conjugated systems, with its first reported use in this context in 2002 30. Since then microwave heating has been used to synthesize a number of conjugated polymers 19, 31–36. One striking finding in all of the prior work is that there was an observed increased rate of polymerization and reduced influence of side reactions, hence higher yields and purer products.…”
Section: Resultsmentioning
confidence: 99%